INTERNALISASI NILAI-NILAI KEISLAMAN BERBASIS WAWASAN KEBANGSAAN DALAM SISTEM PENDIDIKAN - Suud Sarim Karimullah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
This article examines the internalization of Islamic values ​​based on national insight into the education system. While the discussion includes; the application of Islamic values ​​based on national insight and urgency in the education system with the aim that Muslims are always enthusiastic in maintaining Islamic and national values ​​so that they are not easily influenced by various understandings that can threaten the diversity of life in the Pancasila state. Then, the preparation of this article uses a literature study through qualitative descriptive analysis because the information presented is in a descriptive form with an explanation in the form of a statement through an inductive nature. Furthermore, the results of this article state that the application of Islamic values ​​based on national insight can be carried out through the order of personal, family, social, economic, political and national life. Meanwhile, the urgency of its application in the education system aims to remind all elements of the Indonesian nation, including Muslims in particular, that the national education system must adhere to divine values, just and civilized humanity, unity, deliberation and justice, which are essentially in line with various values ​​in Islamic teachings.